Various aspects of the doctor’s quality of life - Leśkiewicz, Michał; Składanek, Justyna; Kopczyńska, Barbara; Cieszkowska, Joanna (Quality in Sport, 2024)
Nowadays, more and more attention is paid to the quality of life. Both private and work-related. More and more actions are taken to improve the quality of life in order to reduce the phenomenon of professional burnout. This significantly improves work efficiency and allows employees to work longer. It is no different in medical professions, including doctors. Fortunately, there is more and more scientific research on this topic. This allowed us to write an illustrative article about various aspects of the doctor’s quality of life. The article will provide information about what quality of life really is and how it is defined. We will present the impact of various factors influencing this, such as length of work, sleep time, age, shift work and work at irregular intervals. We will also show how occupational factors influence health, which translates quite well into life expectancy. It is surprising that doctors have higher than expected risk factors for cardiovascular diseases such as hypertension, hypercholesterolemia, body mass. The cause is usually high stress and lack of time for physical activities after work. Specialization is also important when it comes to life expectancy. Charts with this information about expected age will be presented along with discussion in the text. We hope that in the future there will be further research expanding knowledge on this very important topic. And employers will have developed appropriate standards to improve the quality of life among their employees.